Strategi Pengembangan Pasar Modal Syariah Untuk Mewujudkan Investasi Halal Dalam Mendukung Pertumbuhan Ekonomi Syariah - Uswatun Khasanah; Ahmad Habibi; Muhammad Iqbal Fasa (Advances In Education Journal, 2025)
This study aims to analyze the development strategy of the Islamic capital market in order to realize halal investment that contributes to the growth of the Islamic economy in Indonesia. The Islamic capital market functions to channel funds from the public to productive sectors through investment mechanisms free from riba, gharar, and maisir. The research method used is descriptive qualitative with a library research approach through analysis of scientific literature, regulations, fatwas of the National Sharia Council (DSN-MUI), and policies issued by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX). The results show that clear regulations and innovation of Islamic investment products are crucial to attracting investor interest, while challenges such as a lack of public understanding and competition with conventional products need to be addressed. The development of the Islamic capital market also functions not only as a means of halal investment but also as a key driver of the growth of the Islamic economy that is just, transparent, and oriented towards the welfare of the people. This effort is in line with the objectives of maqāṣid al-syarī‘ah (the principles of Islamic law) to realize economic welfare through an ethical, inclusive, and sustainable financial system.